Aplication of The Elaboration Model to Improve Mathematics Learning Outcomes of Class V Elementary Schools - Ade Sutisna (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve the learning outcomes of class V students in Mathematics learning with the elaboration learning model. The research undertaken was Classroom Action Research through 3 cycles, each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing, and reflecting. In the first cycle the learning completeness index was 77.78%, in the second cycle and cycle it increased to 88.89%. With the class average value of 77.78 in the first cycle, 87.04 in the second cycle and 87.78 in the third cycle. From this classroom action research, it can be concluded that the application of the elaboration learning model can improve student learning outcomes in learning Mathematics on the scale of SD Negeri Panulisan Barat 01, Dayeuhluhur District, Cilacap Regency.